Effect of Dominant Cropping Systems on the Soil Properties in Sirsa District, Haryana: Effect of dominating cropping systems on soil - Verma, Vijendra Kumar; Jakhar, Devender Singh; Raj, Dev; Ranjan, Supriya; Meena, Dileep; Kumar, Sawan; Fagodiya, Ram Kishor; Yadav, Saloni; Patel, Ashish Kumar (Journal of Soil Salinity and Water Quality, 2025)
Lack of information about site-specific nutrients for various cropping systems has been a major challenge in addressing declining soil fertility and improving crop productivity in the Sirsa district, Haryana, India. Therefore, the study was aimed to evaluate and quantify soil properties across cropping systems (CS), including cotton-wheat (C-W), rice-wheat (R-W), groundnut mustard (GN-M), pearl millet-wheat (PM-W), Guar-Mustard (G-W), mungbean-wheat (MB-W), guava orchard, and cotton-mustard (C-M). A total of 140 georeferenced soil samples were collected using a random survey approach, and the samples were analyzed for soil texture, pH, electrical conductivity (EC), organic carbon (OC), available nitrogen percentage (AvN), phosphorus (AvP) and extractable potassium (ExK). The Sulfur Availability Index (SAI) and Soil Nutrient Index (SNI) were also developed. Guava orchard showed the maximum mean value of EC (0.60 dS/m), organic carbon (0.71%), available N (161.70 kg ha-1), AvP (33.91 kg ha-1), available K (325 kg ha-1), and available S (48.52 kg ha-1). Nutrient index values of the all the cropping systems for available N were low, medium for OC except cotton-wheat (low) and available K except guava (high), high for available P except cotton-mustard and guar-mustard (medium) and S except cotton-wheat (medium). Highest SAI was observed in guarva orchard (3.00) whereas minimum was observed in cotton-wheat (2.15). Our findings indicate that cropping systems have huge impact on soil properties.